Understanding Criminal Liability for Pornography in Cyberspace Based on the Pattern of Distribution - Pratiwi, Ratu Indra Kasih (Damhil Law Journal, 2024)
The purpose of this research is that criminal liability for the distribution of sexual intercourse videos cannot be imposed directly on the actor or perpetrator. This is because Law Number 44 of 2008 does not criminalize the act of recording and storing videos of sexual intercourse for personal use. The research method used in this research is a normative research method with a statutory approach, namely by examining all laws and regulations related to the legal issues discussed.Â  Clarified by using a case approach, namely examining other similar cases related to the legal issues being studied. The results of this study Regarding the criminal liability of the actor of the sexual intercourse video scene must be based on proving his guilt in the series of events spreading pornography in the form of a video so that it is believed to be legally subject to punishment. Is it true that the maker wants the pornography in the form of video to be spread to the public space either between electronic media and social media or not at all.